To find equivalent inequalities you have to work the inequality given.
The first step is transpose on of sides to have an expression in one side and zero in the other side:
x - 6 x + 7
--------- ≥ --------
x + 5 x + 3
=>
x - 6 x + 7
--------- - -------- ≥ 0
x + 5 x + 3
=>
(x - 6) (x + 3) - (x + 7) (x + 5)
--------------------------------------- ≥ 0
(x + 5) (x + 3)
=>
x^2 - 3x - 18 - x^2 - 12x - 35
--------------------------------------- ≥ 0
(x + 5) (x + 3)
15x + 53
- ------------------- ≥ 0
(x + 5) (x + 3)
That is an equivalent inequality. Sure you can arrange it to find many other equivalent inequalities. That is why you should include the list of choices. Anyway from this point it should be pretty straigth to arrange the terms until making the equivalent as per the options.
Use a calculator it’s 117
The slope-intercept form is:
y = mx + b
where m = slope, and b = y-intercept.
You need a slope of 1, so m = 1.
You need a y-intercept of -1, so b = -1.
Replace m with 1 and b with -1 in the slope intercept form to get
y = 1x + (-1)
which simplifies to
y = x - 1
We can factor this by using grouping. Take the leading coefficient and multiply it by the constant. In this case we get 5*-7 = -35.
Now we need 2 numbers that add to 2 and multiply to be -35. The numbers are -5 and 7.
So split the 2r into these two terms and group.
(5r^2 - 5r) + (7r - 7)
Factor both groups.
5r(r-1) + 7(r-1)
The factors of (r-1) can be added together to get the answer.
(r-1)(5r+7)